POLITIK HUKUM PIDANA DALAM PERLINDUNGAN TERHADAP KORBAN KEJAHATAN DI INDONESIA - Yulia, Rena (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2012)
Protection of victims of crime is part of the protection of human rights as a whole. The protection that provided was the responsibility of the state that has been manifested in a criminal law policy. The ultimate goal of the criminal law policy is the social defence to achieve the overriding goal of social welfare. Criminal law policy is basically also an integral part of social policy. Criminal Law Policy in Indonesia contained in implementation of the criminal policies through the establishment of statue such as the Penal Code, Criminal Procedure Code, and other organic laws which governing the criminal provisions in it. Criminal Law Policy was emerged from political law which integrated into the criminal policies that embodied in laws governing the criminal provisions. This essay is trying to discuss how criminal law policy in Indonesia that has been implemented, and how the criminal law policy in providing the protection of victims of crime through the criminal justice system in Indonesia. Currently, the criminal law policy regarding the protection of victims of crime has been regulated. But the provisions have not fully provides protection to victims of crime. It can be seen in Act No. 8 of 1981 on the Code of Criminal Procedure Act which gave more protection to the suspect than to the protection of victims. Furthermore, Law No. 13 of 2006 on the Protection of Witnesses and Victims provide better protect witnesses than victims. This is due to the Act appears to provide protection to witnesses incorruption cases. Keywords: the criminal law policy, the criminal justice system, protection of victims of crime.